Classification and Stratification of Pulmonary Embolisms - Russell, Cody; Keshavamurthy, Suresh; Saha, Sibu (International Journal of Angiology, 2022)
Pulmonary embolism remains a leading cause of cardiovascular mortality. Presentation and outcomes are variable among patients and require rapid risk stratification for assessment and prognosis, as well as selection of appropriate treatment. Over the past several decades, several different models and parameters have become available to assess risk and classify pulmonary embolism into different risk categories. Some patients may be candidates for early discharge or complete outpatient treatment, while some may require invasive diagnostics and intensive monitoring. In this review, we summarize contemporary guidelines and methods for classification and risk stratification in an effort to provide tools for physicians to use in their management of patients with acute pulmonary embolisms.
Keywords: pulmonary embolism; classification; stratification; venous thromboembolism; computed tomography pulmonary angiography; RV function; prognostic scoring